1977
DOI: 10.4141/cjas77-073
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Gilts Fed Rapeseed Meal Cv. Tower During Gestation and Lactation

Abstract: Sci. 57: 567-571 (Sept. 1977) soybean meal (SBM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Results from the present study are in agreement with the contemporary research where in, it was observed that 15 to 25% CM could be included in weaned pig diets without any negative effects on growth performance (Landero et al, 2011;Seneviratne et al, 2011;Sanjayan et al, 2014;Parr et al, 2015). In sows, inclusion of 10% rapeseed meal in gestation and lactation diets had no deleterious effect on sow reproductive and suckling piglet performance (Flipot and Dufour, 1977;Quiniou et al, 2012). Quiniou et al (2012) also observed no effect on ADFI in sows fed CM when such diets were formulated on similar NE values.…”
Section: Sow and Litter Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…Results from the present study are in agreement with the contemporary research where in, it was observed that 15 to 25% CM could be included in weaned pig diets without any negative effects on growth performance (Landero et al, 2011;Seneviratne et al, 2011;Sanjayan et al, 2014;Parr et al, 2015). In sows, inclusion of 10% rapeseed meal in gestation and lactation diets had no deleterious effect on sow reproductive and suckling piglet performance (Flipot and Dufour, 1977;Quiniou et al, 2012). Quiniou et al (2012) also observed no effect on ADFI in sows fed CM when such diets were formulated on similar NE values.…”
Section: Sow and Litter Performancesupporting
confidence: 92%
“…Moreover, feeding high fiber diets during pregnancy has shown to reduce aggressive behavior in sows mainly due to reduced hunger (Ramonet et al, 1999;Danielsen and Vestergaard, 2001). Still, the highest recommended inclusion level of CM in diets of lactating sows based on available literature was up to around 20% (Flipot and Dufour, 1977;King et al, 2001;Quiniou et al, 2012).…”
Section: Gestation and Lactation Sow Dietsmentioning
confidence: 99%
“…Considerable advantages have generally been found in the use of low-glucosinolate rapeseed meals. For example, Flipot & Dufour (1977) found that inclusion at IOO g/kg of ration for gestating and lactating gilts caused no significant detrimental effects on reproductive performance or on subsequent performance of their litters. The levels for breeding and other classes of pigs, recommended as a result of Canadian experiences, are shown in Table 3.…”
Section: Availability Of Mineralsmentioning
confidence: 99%